2022
DOI: 10.3390/en15197044
|View full text |Cite
|
Sign up to set email alerts
|

Review of Smart Grid and Nascent Energy Policies: Pakistan as a Case Study

Abstract: Smart grid plays a vital role in energy management systems. It helps to mitigate the demand side management of electricity by managing the microgrid. In the modern era, the concept of hybrid microgrids emerged which helps the smart grid management of electricity. Additionally, the Internet of Things (IoT) technology is used to integrate the hybrid microgrid. Thus, various policies and topologies are employed to perform the task meticulously. Pakistan being an energy deficient country has recently introduced so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The literature review showed that the prevalent course of action taken by researchers has been to focus on the micro scale, on enterprises, especially as regards building competitive advantage of companies and the factors that determine it, e.g., [79,80]. In the case of energy efficiency, the reviewed publications focused on the macro scale (energy efficiency of a country), e.g., [81][82][83]. As regards meso-scale studies, those that discussed assessing the impact of urban policies tended to concentrate on environmental issues and aspects of the health of their citizens, e.g., [84,85].…”
Section: Discussionmentioning
confidence: 99%
“…The literature review showed that the prevalent course of action taken by researchers has been to focus on the micro scale, on enterprises, especially as regards building competitive advantage of companies and the factors that determine it, e.g., [79,80]. In the case of energy efficiency, the reviewed publications focused on the macro scale (energy efficiency of a country), e.g., [81][82][83]. As regards meso-scale studies, those that discussed assessing the impact of urban policies tended to concentrate on environmental issues and aspects of the health of their citizens, e.g., [84,85].…”
Section: Discussionmentioning
confidence: 99%
“…It can be used to operate in some off‐grid places. MGs are found to work best in the Nukundi regions of Katibandar, Jamshoro, Bin Qasim, Gharo, Jhimpir, and Swat 23 …”
Section: Methodsmentioning
confidence: 99%
“…HMGS, hybrid microgrid system. 23 The structure of a solar cell is simple. It is made up of several materials in layers.…”
Section: Methodsmentioning
confidence: 99%
“…Renewable energy sources, such as solar and wind power, produce negligible air pollutants, resulting in cleaner air and reduced health risks associated with poor air quality. In urban areas, where air pollution is particularly severe, microgrids can significantly alleviate this environmental burden [104]. Microgrids can contribute to preserving and enhancing ecosystem services by minimizing land use change, habitat loss, and other environmental impacts associated with large-scale power plants and transmission infrastructure.…”
Section: Environmental Aspects Of Microgrid Projects In Pakistanmentioning
confidence: 99%